2014
DOI: 10.1080/14786419.2014.958738
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and kinetics studies of eugenol and 6-bromoeugenol

Abstract: In this work, we report the antioxidant and free radical scavenging activity of 6-bromoeugenol and eugenol. EC50, the concentration providing 50% inhibition, is calculated and the antioxidant activity index (AAI) is evaluated. The antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging method. EC50 values of 6-bromoeugenol, ascorbic acid and eugenol were 34.270 μg/mL, 54.888 μg/mL and 130.485 μg/mL, respectively. 6-Bromoeugenol showed higher AAI value (1.122) followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…The results of the present study showed ameliorative effects of eugenol in a dose dependent manner against arsenic mediated genotoxicity and oxidative stress. Our results agree with the results of a recent study by Mahboub and Memmou () where eugenol and 6 bromoeugenol has shown antioxidant activity. The antioxidant activity of eugenol was analyzed using 2, 2‐diphenyl‐1 picrylhydrazyl (DPPH) radical scavenging method.…”
Section: Resultssupporting
confidence: 93%
“…The results of the present study showed ameliorative effects of eugenol in a dose dependent manner against arsenic mediated genotoxicity and oxidative stress. Our results agree with the results of a recent study by Mahboub and Memmou () where eugenol and 6 bromoeugenol has shown antioxidant activity. The antioxidant activity of eugenol was analyzed using 2, 2‐diphenyl‐1 picrylhydrazyl (DPPH) radical scavenging method.…”
Section: Resultssupporting
confidence: 93%
“…Eugenol and Clove oil have the ability to scavenge the free radicals [6,[12][13][14]. Eugenol showed inhibition of DPPH radical and hydroxyl radical at concentrations dependent manner.…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%
“…In another study eugenol and 6 bromoeugenol has shown antioxidant activity. [21] The antioxidant activity was analysed using 2, 2-diphenyl-1 picrylhydrazyl (DPPH) radical scavenging method. Anethole has not explored much as eugenol for antigenotoxic and antioxidant potential although in one study Shahat et al [22] have found antioxidant potential of fennel against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%